Worldwide Research Trends on Lung Cancer and Microbiota: A Bibliometric and Visualized Analysis - Ren YF; Tan SY; Wang Q; He JW; You FM; Ma Q; You LT (Journal of Multidisciplinary Healthcare, 2025)
Yi-Feng Ren,1,2,* Shi-Yan Tan,1,* Qian Wang,1 Jia-Wei He,1 Feng-Ming You,1,2 Qiong Ma,1 Li-Ting You3 1Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, 610072, People’s Republic of China; 2TCM Regulating Metabolic Diseases Key Laboratory of Sichuan Province, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, 610072, People’s Republic of China; 3Department of Laboratory Medicine, West China Hospital, Sichuan University, Chengdu, Sichuan Province, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li-Ting You, Department of Laboratory Medicine, West China Hospital, Sichuan University, No. 37 Guoxue Lane, Chengdu, Sichuan Province, 610041, People’s Republic of China, Email youlitin_med@163.com Qiong Ma, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39 Shi-er-qiao Road, Chengdu, Sichuan Province, 610072, People’s Republic of China, Email Maqiong.Dr@outlook.comBackground: The microbiota is intricately linked to lung cancer’s development, progression, diagnosis, and treatment, garnering significant academic interest. This study employs bibliometric methods to trace trends and advancements, emphasizing the extraction and analysis of clinical research data, and outlines current challenges and future research directions.Methods: We selected the literature in the Web of Science Core Collection database. To provide an overview, annual publications, countries/regions, and keywords were evaluated through a bibliometric analysis, and extracted and analyzed key clinical information.Results: A total of 579 publications were reviewed, with 177 clinical studies chosen for detailed analysis. These publications, spanning from 1997 to 2025, showed a consistent yearly increase in the number of articles, despite some fluctuations. Science and PLOS One were the most frequently cited journals in this area. Key contributors to this field include Yan Zhang, Jun Chen, Zoltan Lohinai, and Edit Dulka. China was the leading producer of publications, indicating its close monitoring of the field, though it did not emphasize international collaborations, resulting in less influential publications. Major topics in this field included lung cancer, gut microbiota, microbiome, immunotherapy, inflammation, and biomarkers. Future research will likely focus on biomarkers, machine learning, immunotherapy and mechanisms. Clinical studies have identified common microbiota, such as Prevotella, Bacteroidetes, Streptococcus, Veillonella, and Bacillus, as potential microbial biomarkers.Conclusion: This field has a bright research prospect, and there is a huge unmet clinical need. Future studies need to expand the sample size and further explore microbiota associated with the mechanisms, diagnosis, treatment and prognosis of lung cancer. Solving problems such as small sample size, heterogeneity of the population, sequencing bias, and precise diagnosis, conducting cross-regional and multicenter research, and identifying specific microbiota that have an important impact on cancer treatment are future challenges.Keywords: lung cancer, microbiota, bibliometric